Validação de instrumento de consulta de enfermagem para pessoas com ferida crônica fundamentado na teoria do autocuidado. - Oliveira, Maria José Aguiar de (2019)
Chronic wounds represent an important public health problem, as they interfere in people's productive capacity, generating an increase in early retirements and financial, emotional and social losses. The practice of nursing in the care of these people, must comply with the legal requirements of the profession with the implementation of the Nursing Care Systematization, the Nursing Process and Nursing Consultation. The implementation of this practice requires the use of data recording in a validated instrument, considered an important indicator of nursing care. The general objective of the study was to validate the content and appearance of an instrument for nursing consultation, aimed at people with chronic wounds, based on the conceptual model of Orem's Self-Care Deficit Nursing Theory. The Nursing Theory of Self-Care Deficit consists of three interrelated theoretical constructs: the theory of self-care, the theory of self-care deficit and the theory of the nursing system. It is a methodological, nonexperimental, applied research, with a quantitative approach, composed of four stages: the first consisted of a literature review; the second, describing the first version of the nursing consultation instrument and preparing the second version, structuring the questionnaires for validation and preparing the final version; in the third stage, the content and appearance of the instrument were validated by the five evaluators / judges, and the items were measured using the content index (CI) for clarity and objectivity, with a value of 83.5% and the index content validity (IVC), related to relevance (IVC) with a value of 95%. In the fourth stage, data analysis was performed based on the responses to the questionnaires. The results indicated high agreement between the responses of the judges. It was concluded that the validated instrument, allows the nursing consultation with data collection in a systematic way, allowing selfcare actions by people with chronic wounds.